Locomotor, heart-rate, and metabolic power characteristics of youth women's field hockey: Female Athletes in Motion (FAiM) study - Vescovi, J. D. (Research Quarterly for Exercise and Sport, 2016)
Purpose: The purpose of this study was to quantify the locomotor, heart-rate, and metabolic power characteristics of high-level youth female field hockey matches. Method: Players from the U21 and U17 Canadian women's national teams were monitored during a 4-match test series using Global Positioning System technology. Position (forward, midfielder, defender) and age-group (U21, U17) comparisons were made using 2-way analyses of variance. Results: Forwards played 12 min to 22 min fewer than midfielders and defenders and consequently had lower amounts of total, low-intensity, and moderate-intensity distances. Yet, forwards covered similar amounts of high-intensity running and sprinting distances despite the deficit in playing time. Only 10% to 15% of total distance was characterized by high-intensity running and sprinting, yet the majority of time was spent above 90% maximum heart rate. The distances in high, elevated, and maximal metabolic power categories were greater for U21 than U17 players. Yo-Yo Intermittent Recovery Test performance was related to high-intensity running and maximal metabolic power distance. Conclusions: The current findings highlight positional specificity as well as developmental gaps between age groups for youth female field hockey matches. These match characteristics should be used to assist in establishing appropriate training strategies through the developmental pathway and to assist player achievement to higher standards.